Diffusion of benzene and tetrachloroethylene through saturated cement paste. (25th April 2022) - Hosseini, Payam; McElroy, Amie; Knappe, Detlef R.U.; Gabr, Mohammed; Pour-Ghaz, Mohammad
Highlights: Volatile Organic Compounds (VOCs) are found in water contamination incidents in the US. Benzene and tetrachloroethylene (PCE) are two most prevalent VOCs in contaminated water. Diffusivity of VOCs in cement paste decreases by lowering water to cement ratio. Benzene shows greater diffusivity than PCE in saturated cement paste. Empirical and phenomenological models are proposed to estimate diffusivity of VOCs. Abstract: Diffusion of highly volatile organic compounds (VOCs) through buried concrete infrastructure components, such as pipes and culverts, can occur if these components come in contact with contaminated groundwater or soil. Among various VOCs, benzene and tetrachloroethylene (PCE), are the most common contaminants. This paper aims at measuring the effective diffusion coefficients of benzene and PCE in cement paste. The free diffusion coefficients of VOCs in simulated pore solution were also measured and used in empirical models. Results show that VOCs diffusion coefficients decreased with decreasing w/c because of reduced porosity and increased tortuosity of the pore network as well as increased ionic strength of the pore solution. The increased ionic strength of the pore solution reduced the solubility limit of VOCs in the pore solution and decreased the free diffusion coefficient of VOCs in the pore solution. Also, among all models, phenomenological model provided the most accurate estimates.